The short- and long-term effects of student absence: Evidence from Sweden - Sarah Cattan; Daniel A. Kamhöfer; Martin Karlsson; Therese Nilsson (Institute for Fiscal Studies (IFS), 2021)
Despite the relatively uncontested importance of promoting school attendance in the policy arena, little evidence exists on the causal effect of school absence on long-run socio-economic outcomes. We address this question by combining historical and administrative records for cohorts of Swedish individuals born in the 1930s. We find that absence significantly reduces contemporaneous academic performance, final educational attainment and labor income throughout the life-cycle. The findings are consistent with a dynamic model of human capital formation, whereby absence causes small immediate learning losses which cumulate to larger human capital losses over time and lead to worse labor market performance.
Keywords: C23; I14; I21; I26; 330; Absence in school; educational performance; long-term effects; register data